PERSEPSI PROGRAM PELATIHAN TERHADAP KEMAMPUAN KERJA BAGI ANGGOTA SATPAM PADA PT. TRANSATRISNA MAJU BERSAMA (TANGKAS) PALEMBANG - Tutik Pebrianti; Azizah Humaidah (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2015)
PT Tansatrisna Maju Bersama (Tangkas) Palembang was in Jl. R. Soekamto No. 88 Palembang. This research was done to know the perception of training programs from PT Tansatrisna Maju Bersama (Tangkas) Palembang to their security employability. The writer got research data by conducting observation, direct interviews, and  questionnaire. Based from the observation, training is very important to this company to take on the development of competition in the world of work. Then, to their security it can be increase the quality of human resource in security knowledge, police, social, and management. Training who was given from PT Tansatrisna Maju Bersama (Tangkas) Palembang actually make the great impact to their security employability. Frequently the training given more, then the security will have more employability to do their work activities.